“For Christ Is the End of the Law” (Rom 10:4). Topicality of Religious-Moral Principles of the Old Testament - Muszyński, Henryk (Studia Theologica Varsaviensia, 2020)
“For Christ Is the End of the Law” (Rom 10:4). Topicality of Religious-Moral Principles of the Old Testament